Effects of Waste Plastic on the Physical and Rheological Properties of Bitumen - Abdullah, M.E. (Institute of Physics Publishing, 2017)
Plastic disposal is one of the major problems for developing countries like Malaysia, at the same time Malaysia needs a large network of roads for its smooth economic and social development. The limited source of bitumen needs a deep thinking to ensure fast road construction. Therefore, the use of plastic waste in road construction not only can help to protect environment but also able to help the road construction industry. The aims of this research are to study the effects of waste plastic on rheological properties of bitumen. Modified bitumen was prepared by using blending techniques. Bitumen was heated and plastic waste was slowly added. Rheological properties of bitumen were performance by penetration, softening point, viscosity and direct shear rheometer test. The results showed that when content of plastic waste increase, the penetration value, softening point and viscosity of bitumen also increase. Generally, plastic waste improves the performance of bitumen when it was added into bitumen. It can be said that the usage helps to improve the performance of the road pavement which also reduces the rutting effect. © Published under licence by IOP Publishing Ltd.